Crack monitoring in historical masonry with distributed strain and acoustic emission sensing techniques. (20th February 2018) - Verstrynge, Els; De Wilder, Kristof; Drougkas, Anastasios; Voet, Eli; Van Balen, Koen; Wevers, Martine
Highlights: Qualitative and quantitative comparison of novel techniques for crack monitoring in historical masonry. Crack monitoring in masonry with integrated optical fibres with distributed fibre Bragg grating sensors. Use of masonry surface layout for digital image correlation without speckle pattern. Observation of Felicity effects during AE monitoring on a full-scale masonry wall. Analysis of the effects of temperature fluctuations on monitoring data from a cracked masonry sample. Abstract: The analysis of crack patterns and crack growth is one of the most important steps in the assessment of structural damage in historical masonry. In a search for integrated and accurate monitoring techniques for crack measurements in masonry, several novel techniques based on distributed strain monitoring and acoustic emission (AE) sensing have been investigated in an experimental test campaign. Aim of the test program was to develop integration procedures for the strain and AE sensors, analyse their use for crack monitoring specifically in historical masonry and assess their robustness and efficiency with respect to the experimentally observed crack pattern. The applied techniques were integrated optical fibres with distributed fibre Bragg grating sensors (FBGs), stereo-vision digital image correlation (DIC) without the use of a speckle pattern, optical fibre sensors for acoustic emission sensing (AE-FOS), piezo-electric transducers for acoustic emission sensing (AE-PZT) and LVDTs. While the latter two were applied as reference techniques, the former three were under investigation as novel application. This paper discusses the efficiency of the monitoring techniques with respect to their use in masonry, explains the developed integration procedures, and relates the obtained data sets with the deformations and crack pattern obtained in a full-scale masonry wall test. Additionally, the effects of temperature fluctuations are investigated. The configurations that were developed proved effective for crack monitoring in historical masonry. The highest sensitivity and robustness was observed for the integrated optical fibres with FBGs.